Deciphering basic and key traits of antibiotic resistome in influent and effluent of hospital wastewater treatment systems. (1st March 2023) - Zhu, Lin; Yuan, Ling; Shuai, Xin-Yi; Lin, Ze-Jun; Sun, Yu-Jie; Zhou, Zhen-Chao; Meng, Ling-Xuan; Ju, Feng; Chen, Hong
Highlights: Most antibiotic resistance genes could not be significantly removed by chlorination. Mobile genetic elements potentially influenced the shaping of ARGs in hospital wastewater. The MAGs revealed diverse ARG host pathogenicity and their multi-resistance features. Co-existing patterns of last-resort ARGs and MGEs on MAGs and plasmids were revealed. Abstract: Hospital wastewater treatment system (HWTS) is an important source and environmental reservoir of clinically relevant antibiotic resistance genes (ARGs). However, how antibiotic resistome of clinical wastewater changed in HWTS is poorly understood. Herein, the basic quantitative traits (i.e., diversity and abundance) of ARGs in three HWTSs were profiled by metagenomics. In total, 709 ARG subtypes belonging to 20 ARG types were detected with relative abundance ranging from 1.12 × 10 −5 to 7.33 × 10 −1 copies/cell. Notably, most ARGs could not be significantly removed by chlorination treatment in the HWTS. These ARGs were identified to confer resistance to almost all major classes of antibiotics and include ARGs of last-resort antibiotics, such as bla NDM, mcr and tet (X) which were abundantly occurred in HWTS with 19, 5 and 7 variants, respectively. Moreover, qualitative analysis based on metagenome-assembled genome (MAG) analysis revealed that the putative hosts of the identified ARGs were broadly distributed into at least 8 dominant bacterial phyla. Of the 107 ARG-carrying MAGs recovered, 39 encoded multi-antibiotic resistance and 16 belonged to antibiotic resistant pathogens. Further analysis of co-occurrence patterns of ARGs with mobile genetic elements suggested their potential mobility. These key qualitative traits of ARGs provided further information about their phylogeny and genetic context. This study sheds light on the key traits of ARGs associated with resistance dissemination and pathogenicity and health risks of clinical wastewater. Graphical abstract: Image, graphical abstract